Penerapan Building Information Modeling (BIM) Dalam Analisis Waktu Dan Anggaran Biaya Struktur Dan Arsitektur (Studi Kasus: Gedung Fakultas Ilmu Komputer Universitas Jember) - Irawan, Deliar Ogi Prastica; Trisiana, Anita; Sukmawati, Sri (Indonesian Society of Applied Science, 2021)
The developments in the construction sector are increasing rapidly which makes construction service providers competitors implement an integrated system. Along with the current progress of science and technology, Building Information Modeling (BIM) is present as an integrated system innovation in the form of a digital platform. This study was conducted by analyzing the project of the Faculty of Computer Science, University of Jember using the BIM system. The use of BIM was doing modeling using Revit and scheduling planning used Synchro Pro. The data in this study used secondary data obtained from the Bureau of Planning, University of Jember. The results of the analysis showed that the total budget for the Faculty of Computer Science, University of Jember construction was IDR 7,054,568,108.31 with structural work costs details was IDR 3,448,641,620.63 and architectural work was IDR 3,605,926,487.68. The length of time needed in the construction implementation of the Faculty of Computer Science, University of Jember was 148 days starting from January 1, 2020, until May 27, 2020.